Sleep Quality and Associated Factors among Diabetes, Hypertension, and Heart Failure Patients at Debre Markos Referral Hospital, Northwest Ethiopia. (22nd May 2020) - Edmealem, Afework; Degu, Sr. Genet; Haile, Dessalegn; Gedfew, Mihretie; Bewket, Bekalu; Andualem, Atsedemariam
Abstract : Background . Chronic illnesses have a negative impact on the quality of sleep; however, patients with chronic illness do not bring sleep issues while they are coming to a health institution for a follow-up. As a result, poor sleep quality among patients with chronic illness is often unrecognized and untreated, and it results to a negative impact on the prognosis of chronic illness. Methods . An institutional-based cross-sectional study design was employed from February 22, 2018, to April 6, 2018. The total sample size was 396. The study employed a stratified random sampling technique, and study participants were selected by systematic sampling. The data were collected by a Pittsburgh Sleep Quality Index (PSQI) questionnaire which is a validated and standardized tool. The data were analyzed by SPSS version 25; text, tables, and figures were utilized for data presentation. By considering a 95% confidence level and P value of 0.05, binary logistic regression and Kruskal-Wallis test were enrolled. Results . The prevalence of poor sleep quality among diabetes, hypertension, and heart failure patients was 36.5%. The odds of being a poor sleeper are increased when age increased. Patients who have poor perception towards the prognosis of their illness were four times more likely to be a poor sleeper compared to patients with good perception (AOR = 4.21, 95 % CI = 1.94 ‐ 9.13, P = 0.001 ). Patients who have anxiety were four times more likely to be a poor sleeper compared with patients without anxiety (AOR = 3.69, 95 % CI = 2.19 ‐ 6.20, P = 0.001 ). The educational level and residence were other factors associated with sleep quality. There was a statistically significant difference of sleep quality between patients with diabetes and hypertension, and diabetes and heart failure (F 2, 384 = 10.92, P = 0.004 ). Conclusion and Recommendations . In this study, over one-third of patients had poor sleep quality. Age, educational level, residence, perception towards prognosis of illness, and anxiety were factors associated with sleep quality. All health care providers should assess and provide advice about sleep hygiene and influencing factors. Assessment of sleep quality for every diabetes, hypertension, and heart failure patients in every visit should be incorporated in the care package.